Evaluation of the Nasopharyngeal Microbiota in Beef Cattle Transported to a Feedlot, With a Focus on Lactic Acid-Producing Bacteria - Amat, Samat; Holman, Devin B.; Timsit, Edouard; Schwinghamer, Timothy; Alexander, Trevor W. (Frontiers in Microbiology, 2019)
The nasopharyngeal (NP) microbiota is important in defining respiratory health in feedlot cattle, with certain NP commensals potentially protecting against bovine respiratory disease (BRD) pathogens. In the present study, we evaluated longitudinal changes in the NP microbiota with a focus on lactic acid-producing bacteria (LAB) and their linkage with BRD-associated bacteria in steers (n = 13) that were first transported to an auction market, and then to a feedlot. Deep nasopharyngeal swabs were collected at the farm before transportation to the auction market (d 0), at feedlot placement (d 2), and 5 (d 7) and 12 (d 14) days after feedlot placement. Swabs were processed for the assessment of NP microbiota using 16S rRNA gene sequencing, and for the detection of Mannheimia haemolytica, Pasteurella multocida and Histophilus somni by plating. Possible associations among the 15 most abundant bacterial genera were predicted using a stepwise-selected generalized linear mixed model. Correlations between LAB and BRD-associated Pasteurellaceae families were also assessed. In addition, antimicrobial activity of selected LAB isolates against M. haemolytica was evaluated in vitro. A noticeable shift was observed in the NP microbial community structure, and in the relative abundance of LAB families as a result of auction market exposure, transport and feedlot placement. Varying degrees of positive or negative associations between the 15 most abundant genera were observed. Many of the LAB families were inversely correlated with the BRD-associated Pasteurellaceae family as the cattle were transported to the auction market and then to the feedlot. Nearly all steers were culture-negative for M. haemolytica and H. somni, and P. multocida became less prevalent after feedlot placement. Isolates from the Lactobacillaceae, Streptococcaceae and Enterococcaceae families inhibited the growth of M. haemolytica. The results of this study indicated that the NP microbiota became more diverse with an increase in microbial richness following transport to an auction market and feedlot, and presence of LAB in the nasopharynx may have competitive exclusion effect on BRD-associated pathogens. This study provides evidence of potential cooperation and exclusion taking place in the respiratory microbial community of cattle which may be useful for developing microbial-based strategies to mitigate BRD.